Successful Treatment of Double-Orifice Mitral Stenosis with Percutaneous Balloon Mitral Commissurotomy - Suresh V. Patted; Prabhu C. Halkati; Sameer S. Ambar; Ameet G. Sattur (Case Reports in Cardiology)
Double-orifice mitral valve (DOMV) is an uncommon congenital anomaly, being present in 0.05% of the general population. The isolated occurrence of this anomaly is very rare and, to our knowledge, no data are currently available on the incidence of an isolated DOMV. A DOMV is characterized by a mitral valve with a single fibrous annulus with 2 orifices opening into the left ventricle (LV). Subvalvular structures, especially the tensor apparatus, invariably show various degrees of abnormality. It can substantially obstruct mitral valve inflow or cause mitral valve incompetence. We present a rare case of nineteen-year-old male who underwent percutaneous mitral balloon commissurotomy in stenotic DOMV.